Ghrelin receptor antagonism of hyperlocomotion in cocaine‐sensitized mice requires βarrestin‐2. Issue 1 (7th October 2017) - Toth, Krisztian; Slosky, Lauren M.; Pack, Thomas F.; Urs, Nikhil M.; Boone, Peter; Mao, Lan; Abraham, Dennis; Caron, Marc G.; Barak, Lawrence S.
Abstract: The "brain‐gut" peptide ghrelin, which mediates food‐seeking behaviors, is recognized as a very strong endogenous modulator of dopamine (DA) signaling. Ghrelin binds the G protein‐coupled receptor GHSR1a, and administration of ghrelin increases the rewarding properties of psychostimulants while ghrelin receptor antagonists decrease them. In addition, the GHSR1a signals through βarrestin‐2 to regulate actin/stress fiber rearrangement, suggesting βarrestin‐2 participation in the regulation of actin‐mediated synaptic plasticity for addictive substances like cocaine. The effects of ghrelin receptor ligands on reward strongly suggest that modulation of ghrelin signaling could provide an effective strategy to ameliorate undesirable behaviors arising from addiction. To investigate this possibility, we tested the effects of ghrelin receptor antagonism in a cocaine behavioral sensitization paradigm using DA neuron‐specific βarrestin‐2 KO mice. Our results show that these mice sensitize to cocaine as well as wild‐type littermates. The βarrestin‐2 KO mice, however, no longer respond to the locomotor attenuating effects of the GHSR1a antagonist YIL781. The data presented here suggest that the separate stages of addictive behavior differ in their requirements for βarrestin‐2 and show that pharmacological inhibition of βarrestin‐2 function through GHSR1a antagonism is not equivalent to the loss of βarrestin‐2 function achieved by genetic ablation. These data support targeting GHSR1a signaling in addiction therapy but indicate that using signaling biased compounds that modulate βarrestin‐2 activity differentially from G protein activity may be required. Abstract : Dopamine neuron‐specific βarrestin‐2 KO mice and WT littermates can be sensitized to cocaine to the same extent. In KO mice, however, the ghrelin receptor antagonist YIL781 cannot block cocaine‐induced hyperlocomotion. This demonstrates a selective requirement of βarrestin‐2 activity in the distinct stages of addictive behavior.